Foreign language communicative competence forming of students studying at food production department (by the example of text book “food technology”) - Anna A. Khokhlova; Amaliya L. Kuregyan (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article considers a problem of foreign-language communicative competence forming. Authors believe that training of foreign-language communicative activities with use of course book Food Technology helps students to use and understand foreign-language consciously taking into account a specific communication situation. The book is intended to provide a large amount of specially selected and organized material which allows to use English as the means of communication practically.